Artificial Multisensory Neurons with Fused Haptic and Temperature Perception for Multimodal In‐Sensor Computing. (30th March 2022) - Duan, Qingxi; Zhang, Teng; Liu, Chang; Yuan, Rui; Li, Ge; Jun Tiw, Pek; Yang, Ke; Ge, Chen; Yang, Yuchao; Huang, Ru
Abstract : The human receives and transmits various information from the outside world through different sensory systems. The sensory neurons integrate various sensory inputs into a synthetical perception to monitor complex environments, and this fundamentally determines the way how we perceive the world. Developing multifunctional artificial sensory elements that can integrate multisensory perception plays a vital role in future intelligent perception systems, whereas prior spiking neurons reported can only handle single‐mode physical signals. Herein, a bioinspired haptic‐temperature fusion spiking neuron based upon a serial connection of piezoresistive sensor and VO2 volatile memristor is presented. The artificial sensory neuron is capable of detecting and encoding pressure and temperature inputs based on the voltage dividing effect and the intrinsic thermal sensitivity of metal–insulator transition in VO2 . Recognition of Braille characters is achieved through multiple piezoresistive sensors, taking advantage of the spatial integration capabilities of such spiking neurons. Notably, the traditionally separate haptic and temperature signals can be fused physically in the sensory neuron when synchronizing the two sensory cues, which is able to recognize multimodal haptic/temperature patterns. The artificial multisensory neuron thus provides a promising approach toward e‐skin, neurorobotics, and human–machine interaction technologies. A preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.164668806.60849882 . Abstract : Herein, a bioinspired haptic‐temperature fusion spiking neuron based on a combination of piezoresistive sensor and VO2 volatile memristor is demonstrated. The thermal characteristics of VO2 memristor and mechanical sensory properties of the piezoresistive sensor are exploited and combined in the same component, enabling multimodal in‐sensor computing. This can provide a promising approach toward e‐skin, neurorobotics, and human–machine interaction technologies.